Goodness: Attributive and predicative - Turp, Michael-John (Les ateliers de l'éthique / The Ethics Forum, 2016)
There is little consensus concerning the truth or reference conditions for evaluative terms such as “good” and “bad.” In his paper “Good and Evil,” Geach (1956) proposed that we distinguish between attributive and predicative uses of “good.” Foot (2001), Thomson (2008), Kraut (2011), and others have put this distinction to use when discussing basic questions of value theory. In §§1-2, I outline Geach’s proposal and argue that attributive evaluation depends on a prior grasp of the kind of thing that is evaluated, which is another way of saying a prior grasp of a thing’s nature. In §§3-4, I discuss the evaluation of artifacts, which provide the clearest examples of attributive evaluation. This allows me to address a series of problems apparently facing the idea of attributive goodness. In §5, I consider the neo-Aristotelian idea that we can extend attributive accounts of goodness to human lives, and I pay attention to Foot’s account of natural goodness. This leads me to consider the goodness of human life as a whole in §6. At this point. I depart from Geach’s approach and argue that questions of attributive goodness finally give rise to questions of predicative or absolute goodness.